The Effect of Green Accounting and Environmental Disclosure on Financial Performance - Salsabila, Vania; Munari (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
The present study investigates the effect of green accounting and environmental disclosure on the financial performance of transportation and logistics companies listed on the Indonesian Stock Exchange (IDX) between 2020 and 2023. A quantitative approach was utilized to assess 18 companies that were selected through purposive sampling. A total of 72 data were obtained from annual and sustainability reports and analyzed using multiple linear regression. The findings indicate that green accounting as well as environmental disclosure have a positive and significant effect on financial performance. The study offers practical implications: sustainable practices, including green accounting and environmental disclosure, may enhance stakeholder trust and strengthen financial outcomes.